2022
DOI: 10.1007/s40534-022-00282-1
|View full text |Cite
|
Sign up to set email alerts
|

Measured load spectra of the bearing in high-speed train gearbox under different gear meshing conditions

Abstract: The load spectrum is a crucial factor for assessing the fatigue reliability of in-service rolling element bearings in transmission systems. For a bearing in a high-speed train gearbox, a measurement technique based on strain detection of bearing outer ring was used to instrument the bearing and determine the time histories of the distributed load in the bearing under different gear meshing conditions. Accordingly, the load spectrum of the total radial load carried by the bearing was compiled. The mean value an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has been found that hunting motions (self-excited oscillation due to instability) significantly affect the vibration and stress of car bodies (Li, Wu, Liu, Wu, & Zeng, 2022) and bogie frames (Qu, Wang, Zhang, Li, & Wei, 2021) and further reduce their fatigue life. Meanwhile, wheel polygonization (periodic out-of-roundness) has been found to affect the vibration and stress of bogie frames (Sun, Wei, Liu, Dai, Qu, & Zhao, 2022), wheel axles (Zhang, Wang, Zhang, Zhu, & Yang, 2021) and bearings (Wang, Allen, Mei, Wang, Yin, & Zhang, 2019; Hou et al. , 2023) and further reduce their fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that hunting motions (self-excited oscillation due to instability) significantly affect the vibration and stress of car bodies (Li, Wu, Liu, Wu, & Zeng, 2022) and bogie frames (Qu, Wang, Zhang, Li, & Wei, 2021) and further reduce their fatigue life. Meanwhile, wheel polygonization (periodic out-of-roundness) has been found to affect the vibration and stress of bogie frames (Sun, Wei, Liu, Dai, Qu, & Zhao, 2022), wheel axles (Zhang, Wang, Zhang, Zhu, & Yang, 2021) and bearings (Wang, Allen, Mei, Wang, Yin, & Zhang, 2019; Hou et al. , 2023) and further reduce their fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the force increased with vibration acceleration, rotation speed, and radial load. Suzuki et al 8 and Hou et al 9 measured the rolling element loads of pinion bearings for railway gear units under actual traction torque. These studies reveal the vibration and force interactions of the components inside the bearing.…”
Section: Introductionmentioning
confidence: 99%